STRATEGI PEMASARAN KERUPUK IKAN GABUS STUDI KASUS INDUSTRI RUMAHTANGGA SENTANI BAROKAH DISTRIK SENTANI KABUPATEN JAYAPURA - Tasriani, Evi (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
Determination of the location of this research is done purposively. This research was conducted at the Sentani Barokah Home Industry with the consideration that one of them is working on cork fish crackers in Sentani District, Jayapura Regency. The research time is June to July 2022. This study aims to: 1. To find out the marketing mix used in the Sentani Barokah Home Industry. 2. To determine the internal and external factors faced and alternative strategies that can be used in product marketing. The results showed that the Sentani Barokah Home Industry had implemented a marketing mix strategy. The components in the industry's marketing mix are product, price, distribution, and promotion. The scoring results obtained from internal and external factors in the marketing strategy of snakehead fish crackers for the Sentani Barokah Home Industry are in the form of a strength factor of 2.86 and a weakness of 1 .84 and then reduced by the criteria of strength and weakness so that the coordinate value is 1.02. Furthermore, the threat factor and industrial opportunity are in the form of an opportunity factor of 4.3 and a threat of 2.55 so that the coordinate value is 1.75. An alternative strategy that can be used in marketing at Sentani Barokah's home industry is the S-O (Strength-Opportunity) strategy, which can take advantage of government support in expanding the marketing distribution network considering the market opportunities are still open and very wide